2016
DOI: 10.1016/j.msec.2016.07.081
|View full text |Cite
|
Sign up to set email alerts
|

In vitro analysis of different properties of acrylic resins for ocular prosthesis submitted to accelerated aging with or without photopolymerized glaze

Abstract: The effect of a photopolymerized glaze on different properties of acrylic resin (AR) for ocular prostheses submitted to accelerated aging was investigated. Forty discs were divided into 4 groups: N1 AR without glaze (G1); colorless AR without glaze (G2); N1 AR with glaze (G3); and colorless AR with glaze (G4). All samples were polished with sandpaper (240, 600 and 800-grit). In G1 and G2, a 1200-grit sandpaper was also used. In G3 and G4, samples were coated with MegaSeal glaze. Property analysis of color stab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 42 publications
0
22
0
Order By: Relevance
“…A previous study of Santos et al . () related that the surface energy of the ocular acrylic resins submitted to glaze application did not differ from the groups which received mechanical polishing, but an increase in surface energy was observed only on N1 acrylic resin after ageing. Thus, we believe that these two studies can be considered complementary, since this study showed the greater roughness value for the N1 AR group with glaze after ageing, and the previous one showed greater surface energy values for this group, independent of the treatment.…”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…A previous study of Santos et al . () related that the surface energy of the ocular acrylic resins submitted to glaze application did not differ from the groups which received mechanical polishing, but an increase in surface energy was observed only on N1 acrylic resin after ageing. Thus, we believe that these two studies can be considered complementary, since this study showed the greater roughness value for the N1 AR group with glaze after ageing, and the previous one showed greater surface energy values for this group, independent of the treatment.…”
Section: Resultsmentioning
confidence: 95%
“…First, the groups had showed similar contact angles in our previous study (Santos et al . ). Second, the surface roughness values of acrylic resins submitted to Staph.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations